Pengembangan Media Pantabtang Untuk Meningkatkan Sikap Tanggung Jawab Anak Kelompok B Di TK PKK Ngadri - Fitri, Nurlailatul; Nindiya , Devi Candra; Farantika, Dessy (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
Media are objects that can be manipulated, observed, listened to, read, or talked about using certain tools. Therefore, learning media are various useful forms, both physical and technical, which can help teachers in conveying learning material to students. At the Ngadri PKK Kindergarten educational institution, especially group B, there are still many students who lack a responsible attitude, especially towards themselves. After the researcher carried out a needs analysis of the problems that emerged in group B children, here the researcher took the initiative to develop a PanTabTang media (Star Savings Board). This media was developed as an alternative in increasing the responsible attitude of group B children at the Ngadri PKK Kindergarten. The aim of this research and development is to test the level of validity, practicality and effectiveness of the PanTabTang media for group B children at PKK Ngadri Kindergarten. This research and development uses the ADDIE development model which goes through 5 stages, namely 1) Analysis; 2) Design; 3) Development; 4) Implementation; 5) Evaluation. The research and development results show that the first media expert obtained a score of 100% from the first media expert, the second media expert obtained a score of 91.67%, and from the teacher response questionnaire sheet he obtained a score of 95.56%. The results of product trials from student observation sheets achieved a normalized gain value of 0.81.